Exploring how the dark triad and curiosity shape the trajectory of affective events in response to COVID-19 stress and psychological well-being: A three-way interaction model - Junça Silva, A.; Lopes, M. (Social Sciences, 2024)
Background: The present research relied on the affective events theory to develop a framework explaining how daily micro-events trigger affective reactions that, in turn, influence quality-of-life indicators (i.e., psychological well-being and COVID-19 stress). We further delineated theoretical arguments for curiosity as a boundary condition that moderated this relation and proposed the dark triad (Machiavellianism, narcissism, and psychopathy) as a threatening factor. Methods: We conducted two studies to test the model. Study one analyzed the moderated mediation model regarding COVID-19 stress (n = 241), and study two (n = 653) analyzed the model regarding psychological well-being as the outcome. Results: Study one demonstrated that daily hassles increased COVID-19 stress via a negative effect, but this was not contingent on the levels of curiosity and the dark triad traits. However, the mediating path of positive affect between daily uplifts and COVID-19 stress was conditional upon the levels of curiosity and the dark triad traits (Machiavellianism and psychopathy), such that when individuals scored high on curiosity and dark traits, the indirect effect became stronger. The results showed that narcissism did not moderate the moderated mediation relationship. Study two showed that daily uplifts boosted psychological well-being through positive affect, and this relation was dependent on curiosity and on the three dark traits, such that it became weaker as curiosity decreased and the dark triad traits increased. We also found that daily hassles, by triggering negative affect, decreased psychological well-being, in particular for those who scored lower on curiosity and higher on psychopathy and narcissism (but not for Machiavellianism). Conclusions: Overall, COVID-19 stress seems to be more responsive to daily hassles than to daily uplifts. Nevertheless, when daily uplifts are factored in, they foster a sense of well-being that helps reduce COVID-19-related stress, especially in individuals who are naturally curious and exhibit high levels of Machiavellian and psychopathic traits. Conversely, psychological well-being appears to be more influenced by situational factors, as it is affected by both types of daily micro-events. We discuss the implications of both studies in light of the affective events theory.